Dieu créateur, Seigneur du ciel et de la terre, dans le livre des Actes - Siffer, Nathalie 1970- (2025)
By examining the fundamental elements of his conception of God, we can see that Luke comes to superimpose creative act and sovereign action. This contribution will seek to determine how he expresses the lordship of the Creator, or more precisely how the representation of God the Creator is linked to the expression of his sovereignty. Four passages from the book of Acts will be studied from this angle, each of which, in its own way, displaying the image of a God manifesting his lordship in and over his creation: Acts 4:24 ; 7:49-50 ; 14:15 ; 17:24. These statements also bear witness to a veritable network, sublimating this God who reveals himself to be both artisan and master of the creation, while placing it within the history of salvation that he himself initiated.
En examinant les éléments fondamentaux de sa conception de Dieu, on observe que l'auteur lucanien en vient à superposer acte créateur et agir souverain. Cette contribution s'attachera à déterminer comment il exprime la seigneurie du Créateur, ou plus exactement comment la représentation du Dieu créateur s'articule à l'expression de sa souveraineté. Seront étudiés sous cet angle quatre passages du livre des Actes qui affichent, chacun à sa façon, l'image d'un Dieu manifestant sa seigneurie dans et sur sa création : Ac 4, 24 ; 7, 49-50 ; 14, 15 ; 17, 24. Ces énoncés témoignent en outre d'une véritable mise en réseau, sublimant ce Dieu qui se révèle à la fois artisan et maître de la création tout en l'inscrivant dans l'histoire du salut qu'il a lui-même initiée.
Keywords: Ac 14:15; Ac 17:24; Ac 4:24; Ac 7:49-50; Acts 14:15; Acts 17:24; Acts 4:24; Acts 7:49-50; Dieu créateur; God the creator; Lukan works; Creation; Création; divine sovereignty; souveraineté divine; œuvre lucanienne